The Role of Application of Standards on Economic Growth and Its Assessment: Case Study of Azerbaijan Republic - Huseynova, Arzu; Hajiyeva, Aytaj; Mazanova, Ophelya; Huseynov, Safar; Mustafayev, Emin (Journal of Ecohumanism, 2025)
This study examines the effectiveness of standards on economic growth based on the data for Azerbaijan Republic by using regression analysis method. First and foremost, we have answered some questions, like ‘what is standard? Why the standard is needed? etc.” and investigated the essence of the standardization concept. Our goal is to evaluate the effects of the implementation of standards on the economic growth of Azerbaijan using world experience and to develop recommendations for the direction of the application of standards, to provide and support proposals for the improvement of the normative legal framework for the application of standards. To evaluate the effects of standards on economic growth in Azerbaijan, the Cobb-Douglas production function was used based on the data of the State Statistical Committee of the Republic of Azerbaijan and the Azerbaijan Standardization Institute. The research result confirm that the gas station standards had a positive impact on GDP, while the GOST standards had a negative impact. The cumulative effect of both is positive. Initially, we can say that increasing the number of standards by one percent increases GDP by 0.84%. Since there is no field assessment database, no such assessment was conducted.